2016
DOI: 10.1016/j.jid.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

TSLP Is a Potential Initiator of Collagen Synthesis and an Activator of CXCR4/SDF-1 Axis in Keloid Pathogenesis

Abstract: Recently, thymic stromal lymphopoietin (TSLP), which is well studied in allergic diseases, has been reported in fibrotic diseases, including idiopathic pulmonary fibrosis and atopic dermatitis fibrosis. However, the role of TSLP in keloid is obscure. In this study, we assessed the expression of TSLP in keloid tissue and investigated the possible role of TSLP in keloid pathogenesis. We observed that TSLP expression was increased in keloid tissue compared to normal tissue. Furthermore, TSLP treatment induced inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…TSLP is expressed in a broad spectrum of diseases. This is the case of AD (Soumelis et al, 2002), psoriasis (Volpe et al, 2014), NS (Hovnanian, 2013; Furio and Hovnanian, 2014), keloid (Shin et al, 2016), and helminthic infections (Ramalingam et al, 2009; Ziegler and Artis, 2010; Giacomin et al, 2012). In some of these diseases, Tfh cells have been reported (Glatman Zaretsky et al, 2009; Niu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…TSLP is expressed in a broad spectrum of diseases. This is the case of AD (Soumelis et al, 2002), psoriasis (Volpe et al, 2014), NS (Hovnanian, 2013; Furio and Hovnanian, 2014), keloid (Shin et al, 2016), and helminthic infections (Ramalingam et al, 2009; Ziegler and Artis, 2010; Giacomin et al, 2012). In some of these diseases, Tfh cells have been reported (Glatman Zaretsky et al, 2009; Niu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression for TSLP displayed the highest FC m in undifferentiated tripotent clonal cultures compared cultures that did not comprise chondrogenic differentiation. For keloid firboblasts TSLP is described as a potent inducer of collagen and TGF-β production [19]. Among the other 52 genes with different gene expression is Transforming Growth Factor beta Type III Receptor ( TGFBR3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our group observed a clear dual effect with proinflammatory and profibrotic signatures in vitro and in vivo (Christmann et al, 2013). Another piece of the puzzle that Shin et al (2016) revealed was that the profibrotic effect of TSLP seems to be dependent on TGF-b, at least in dermal fibroblasts. The question still remains concerning whether TSLP profibrotic effects are TGF-b dependent in vivo, although our unpublished studies are pointing to the same direction.…”
Section: Thymic Stromal Lymphopoietin Involvement In Fibrosismentioning
confidence: 80%
“…Several mechanisms have been proposed to play roles in the development of keloids. Shin et al (2016) report novel pathways that play roles in this complex disease.…”
Section: Romy Beatriz Christmannmentioning
confidence: 99%
See 1 more Smart Citation